Global landscape assessment of screening technologies for medicine quality assurance: stakeholder perceptions and practices from ten countries - Lukas Roth; Ameena Nalim; Beth Turesson; Laura Krech (BMC, 2018)
Abstract Background The spread of substandard and falsified (SF) medical products constitutes a growing global public health concern. Some countries use portable, handheld screening technologies (STs) in the field to accelerate detection of SF medicines and reduce the number of medicine samples that undergo costly and time-consuming confirmatory analysis. Methods A multi-country, multi-stakeholder landscape assessment utilizing qualitative methodology was used to examine practices and perceptions related to the use of STs. Qualitative interview guides were designed using the results of a literature review and comprised of open-ended questions with the study participants, who were from national medicine regulatory authorities, pharmaceutical manufacturers, pharmacies, and distributors. Ten geographically and economically diverse countries were selected: Argentina, China, Egypt, India, Jordan, Mexico, Nigeria, Philippines, the United States, and Zimbabwe. Of the completed 53 interviews, 32 were in-person, 16 were phone interviews, and 5 were via written questionnaires. Results Data analysis shows a wide variation in understanding and usage of STs in different sectors. Virtually all of the study participants indicated a lack of objective, accessible information on STs to advise them on what technologies would be beneficial for their needs. Study participants also described their ideal capabilities of the next generation of STs, including shareable spectral libraries, lower acquisition costs, lesser training requirements, and in-country maintenance and technical support. Conclusion The results and recommendations presented in this article can be used to help regulators communicate and justify their needs to acquire and invest in new STs. There is a need for additional standardized, trustworthy and scientifically sound evaluations of STs, and to support regulators to effectively deploy the most promising technologies. ST manufacturers can take into account some of the limitations of the technologies the interviewees identified in this article, such as a dearth of technologies, which provide quantitative information about the active ingredient, and take steps to address them to better serve their customers. These results and recommendations, can catalyze research and actionable interventions into the development, review, application, and use of STs.